Countdown to midnight eaudiobook A novel. - Brown, Dale (Nick Flynn, 2022)
In this sequel to Dale Brown's New York Times bestselling Arctic Storm Rising, former U.S. Air Force officer Nick Flynn is caught up in a shadow war against allied Russia and Iran—a duo wielding a terrifying new weapon. Nick Flynn is back in action, and he has a new employer—a shadowy intelligence outfit whose roots go back to the very beginning of the Cold War. But his first mission for them almost becomes his last. While meeting with a high-ranking Iranian dissident in the Austrian Alps, Flynn is ambushed and nearly killed... just after learning that Iran and Russia are working together on a mysterious project—one they have codenamed MIDNIGHT. Flynn is determined to uncover MIDNIGHT's lethal secrets. Why are Moscow and Tehran covertly retrofitting a massive oil tanker in an Iranian port? What purpose lies behind their closely guarded effort, the brainchild of Pavel Voronin—a ruthless billionaire allied with Russia's autocratic president? Flynn and his new team plan to put an end to the nefarious project, but they're dogged at every step by Voronin's hired Raven Syndicate killers—elite veterans of Russia's special forces and intelligence services. As they track the enemy from the streets of Vienna to deep inside hostile Iran, Flynn and his crew must repeatedly risk their lives to pierce the layers of deception around this shadow war. It's a race against time to stop Voronin from launching his terrifying new weapon against the United States—potentially killing hundreds of millions and overturning the world's balance of power forever. The odds are stacked high against Flynn and his team... but that's never stopped Nick before. Supplemental enhancement PDF accompanies the audiobook.